2013
DOI: 10.1016/j.jssas.2012.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of pollen collected by honey bee, Apis mellifera L. colonies at Fayoum Governorate, Egypt. Part 1: Botanical origin

Abstract: The present work is the 1st part of 3-part study carried out at Fayoum Governorate, Egypt to evaluate the pollen species collected by honey bee, Apis mellifera L., colonies during two successive years, 2009 and 2010. Obtained results showed that, in 2009, total amount of trapped pollen (fresh weight) was 2354.89 g/colony/year (mean 588.72 g/colony/season), with peaks in summer and spring, while declined in autumn and winter. Correlation between mean maximum and minimum temperatures and weekly pollen weights wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
9
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 4 publications
4
9
1
Order By: Relevance
“…That is might be due to increasing of temperature in summer than spring and autumn season, and increasing the flora in this time. These results are agree with Ismail et al (2013) who found that the mean amount of trapped pollen was 588.72 g/colony/season), with detection of high peaks in summer and spring .…”
Section: Seasonal Average Amount Of Collected Pollensupporting
confidence: 93%
“…That is might be due to increasing of temperature in summer than spring and autumn season, and increasing the flora in this time. These results are agree with Ismail et al (2013) who found that the mean amount of trapped pollen was 588.72 g/colony/season), with detection of high peaks in summer and spring .…”
Section: Seasonal Average Amount Of Collected Pollensupporting
confidence: 93%
“…1) were unfavourable for pollination resulting in a significant reduction in seed yields of cutting treatments T3 and T4 (Table 1) compared to T2 when environmental conditions were more favourable for pollination. These findings were in line with the studies that reported temperatures of 28-32 °C with a relative humidity of 45-55%, which were favourable for maximum pollination in berseem clover crops 32,33 . The timing of the last forage cut prior to seed harvesting can also impact on the efficiency of pollinators, namely honeybees.…”
Section: Discussionsupporting
confidence: 92%
“…This limits the use of these data with respect to forecasting collection levels. Further, collection by any one colony is expected to vary temporally over the course of a year (Rashad and Parker 1958;Forcone et al 2011;Ismail et al 2013;Requirer et al 2015).…”
Section: Collection Storage and Consumption Of Pollen By Coloniesmentioning
confidence: 99%